Gradual Carotid Artery Stenosis in Mice Closely Replicates Hypoperfusive Vascular Dementia in Humans. Issue 2 (February 2016) - Hattori, Yorito; Enmi, Jun‐ichiro; Iguchi, Satoshi; Saito, Satoshi; Yamamoto, Yumi; Tsuji, Masahiro; Nagatsuka, Kazuyuki; Kalaria, Rajesh N.; Iida, Hidehiro; Ihara, Masafumi
Abstract : Background: Existing rodent models of vascular cognitive impairment (VCI) show abrupt changes in cerebral blood flow (CBF) and do not reliably replicate the clinical pathogenesis of VCI. We therefore aimed to develop a mouse model of VCI where CBF is gradually reduced, followed by subsequent progressive motor and cognitive impairment, after surgical intervention. Methods and Results: Adult C57BL/6J male mice were subjected to gradual common carotid artery stenosis (GCAS) surgery by using an ameroid constrictor vessel‐constricting device with an inner diameter of 0.75 mm. The common carotid arteries narrowed gradually after gradual constriction of ameroid constrictors over 28 days after GCAS, with subsequent 79.3% area stenosis as a result of smooth muscle cell proliferation and macrophage infiltration in the tunica intima. The 28‐day survival rate was 91%. Arterial spin labeling demonstrated gradual and continuous reduction of cortical and subcortical CBF (ratio to the preoperative value) to 54.6% and 51.5%, respectively, over 28 days. However, magnetic resonance angiography showed increment of collateral flow signals in the leptomeningeal artery. Rarefaction and proliferation of astrocytes and microglia, with loss of oligodendrocytes, were found in the white matter at 32 days. Hippocampal neuronal loss was observed in only 25% of GCAS mice, consistent with lack of abnormalities in the Morris water maze test. The rotarod test showed motor impairment, and the Y‐maze test showed working memory deficits. Conclusions: The GCAS model successfully generated gradual and continuous CBF reduction over 28 days, with replication of key histological, radiological, and behavioral features associated with cerebral hypoperfusion leading to VCI.